Whistleblowers: Implications for Corporate Governance - Deborah A. DeMott (Washington University Law Review, 2021)
Focusing primarily on internal whistleblowing, this article argues that incorporating whistleblowers into formal governance structures could spur more proactive involvement by directors in monitoring compliance with law and regulation. The article opens by examining questions of definition, contingency, duty, and motivation that are associated with whistleblowing. The next portion of the article briefly surveys the patchwork that comprises whistleblowing law in the United States, stressing that highly salient scandals generally precede the adoption of whistleblowing regimes. Against this background, the article turns to corporate law and governance in the United States, arguing that both are more dynamic and less static than some academic accounts assume. Nothing inherent to either corporate law or governance bars the formal incorporation of mandated whistleblower protection into organic organizational law. Directors’ duties of loyalty under contemporary Delaware law encompass invigorated oversight of legal and regulatory compliance. The link between the information revealed by internal whistleblowing and directors’ duties of loyalty strengthens the argument for treating whistleblowing as a component of corporate governance that should be formalized via organizational law.
Keywords: Corporate law; Corporate governance; Whistleblowers; Corporate director duties; Organizational law